2002
DOI: 10.1007/s00417-002-0517-4
|View full text |Cite
|
Sign up to set email alerts
|

Dose-related structural effects of photodynamic therapy on choroidal and retinal structures of human eyes

Abstract: PDT with verteporfin at a dosage used clinically induces selective occlusion of the physiological choriocapillaris without affecting deeper choroidal, retinal, and optic nerve vessels or the overlying retinal pigment epithelium and neurosensory retina. The main mechanism of action appears to be vascular thrombosis induced by cytotoxic damage of endothelial cells and platelet activation. An increase in light dose enhances the occlusive effect with thrombosis within deeper choroidal layers and damage to the reti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
154
1
6

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(168 citation statements)
references
References 18 publications
7
154
1
6
Order By: Relevance
“…Although randomized trials comparing an intravitreal triamcinolone acetonide monotherapy with a combination of intravitreal triamcinolone acetonide and photodynamic therapy for the treatment of exudative age-related macular degeneration have not been published yet, and although photodynamic therapy may lead to a collateral tissue damage in the macula in contrast to intravitreal triamcinolone acetonide, 36 the present study in combination with results published in the literature may suggest that the combined treatment consisting of verteporfin photodynamic therapy and intravitreal triamcinolone acetonide may be superior to the intravitreal triamcinolone acetonide monotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Although randomized trials comparing an intravitreal triamcinolone acetonide monotherapy with a combination of intravitreal triamcinolone acetonide and photodynamic therapy for the treatment of exudative age-related macular degeneration have not been published yet, and although photodynamic therapy may lead to a collateral tissue damage in the macula in contrast to intravitreal triamcinolone acetonide, 36 the present study in combination with results published in the literature may suggest that the combined treatment consisting of verteporfin photodynamic therapy and intravitreal triamcinolone acetonide may be superior to the intravitreal triamcinolone acetonide monotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that cytotoxicity and vascular damage associated with PDT are dose dependent. 25,26 In this prospective clinical trial, we compared the efficacy and safety of 1/2 PDT with those of 1/3 PDT for chronic CSC. Zhao et al 20 conducted PDT with verteporfin at 30% of the conventional dosage in 8 eyes with acute CSC, and all eyes (100%) had resolution of SRF.…”
Section: )mentioning
confidence: 99%
“…This is confirmed by many experimental studies. E.g., an electron microscopic study on the Verteporfin PDT effects on choroidal and retinal structures in the hum eye clearly showed swelling, shrinking and fragmentation of the choriocapillary endothelium, basement detachment, and ultimately thrombus formation [101]. Similar results were obtained with a liposomal formulation of a (phthalocyaninato)zinc(II) derivative [102].…”
Section: Age-related Macular Degenerationmentioning
confidence: 56%